2020
DOI: 10.1002/anie.202008369
|View full text |Cite
|
Sign up to set email alerts
|

Carbene‐Catalyzed Enantioselective Aldol Reaction: Post‐Aldol Stereochemistry Control and Formation of Quaternary Stereogenic Centers

Abstract: The dominated approaches for asymmetric aldol reactions have primarily focused on the aldol carbon-carbon bond-forming events. Here we postulate and develop a new catalytic strategy that seeks to modulate the reaction thermodynamics and control the product enantioselectivities via postaldol processes. Specifically, an NHC catalyst is used to activate a masked enolate substrate (vinyl carbonate) to promote the aldol reaction in a non-enantioselective manner. This reversible aldol event is subsequently followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The absolute configuration of 3 e was confirmed by X-ray analysis. [19] Introducing a chloride atom or a trifluoromethyl group at the 6-position of isatins did not affect the reaction outcomes, with 3 l and 3 m formed in high yields, excellent diastereo-and enantioselectivities. Isatins bearing a fluoride atom or a methyl unit at the 7-position reacted effectively to give 3 n and 3 o with similar results.…”
Section: Resultsmentioning
confidence: 96%
“…The absolute configuration of 3 e was confirmed by X-ray analysis. [19] Introducing a chloride atom or a trifluoromethyl group at the 6-position of isatins did not affect the reaction outcomes, with 3 l and 3 m formed in high yields, excellent diastereo-and enantioselectivities. Isatins bearing a fluoride atom or a methyl unit at the 7-position reacted effectively to give 3 n and 3 o with similar results.…”
Section: Resultsmentioning
confidence: 96%
“…The aldol reaction is a basic transformation in creating new carbon–carbon bonds and β-hydroxyl carbonyl compounds. 59 Considering the higher stability and catalytically active sites (unsaturated transition metals) on the Al 4 O 4 support, three representative AlOCs ( AlOC-99 , AlOC-109 and AlOC-112 ) were used as catalysts for the direct aldol reaction of acetone and nitro-substituted aromatic aldehyde in DMSO. The catalytic results are summarized in Table S6 †…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Chi et al reported cleverly designed NHC-catalyzed asymmetric aldol reactions of benzofuran-2-carbonates 102 and oxazole-2-carbonates 103. [53] These reactions involve asymmetric dearomatization of the benzofuran and oxazole moieties and give products 104 in yields up to 98 % with excellent enantioselectivities (up to 99 % er) and diastereoselectivities (up to > 20 : 1 dr). They also successfully explored the reaction of O-acylated azlactones 108 and isatins 109 which demonstrated the generality of this strategy (Scheme 28).…”
Section: Cascade Dearomatization Reactionsmentioning
confidence: 99%